2021
DOI: 10.4236/ojn.2021.113017
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Treatment by Patients with Type 2 Diabetes Mellitus at Monze Mission Hospital, Monze, Zambia

Abstract: Background: Diabetes mellitus (DM) is one of the most common noncommunicable diseases and among the leading causes of disability, morbidity and mortality globally. The study assessed adherence to treatment by type 2 DM patients aged 20 years and above at Monze Mission Hospital in Monze district, Zambia. Research questions: 1) What is the level of adherence to treatment by type 2 DM patients receiving care from Monze Mission Hospital? 2) What factors influence adherence to treatment by type 2 DM patients? Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…[34] This high non-adherence to medication, diet and exercise regime mirrors the situation across many countries in the region and Africa in general. For instance, studies done in Africa which showed low level of adherence include Botswana at 41.8%, [35] Zambia at 44.2%, [12] Ghana at 53.5%, [36] Nigeria at 50.2% at 34.0%, [37] Ethiopia, [38] Uganda at 38.1%, [39] and Tanzania at 60.2%, [40]. This is a concern particularly because the rate of type 2 diabetes in Africa is on the rise where it was 24 million in 2021 and is projected to reach 33 million by 2030.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] This high non-adherence to medication, diet and exercise regime mirrors the situation across many countries in the region and Africa in general. For instance, studies done in Africa which showed low level of adherence include Botswana at 41.8%, [35] Zambia at 44.2%, [12] Ghana at 53.5%, [36] Nigeria at 50.2% at 34.0%, [37] Ethiopia, [38] Uganda at 38.1%, [39] and Tanzania at 60.2%, [40]. This is a concern particularly because the rate of type 2 diabetes in Africa is on the rise where it was 24 million in 2021 and is projected to reach 33 million by 2030.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] In the same setting the level of adherence to medication ranges from 40% to 75%. [10][11][12][13][14] Poor adherence and rising occurrence of type 2 diabetes mellitus risk factors (alcohol consumption, smoking, overweight/ obesity, physical inactivity) are believed to be the key deterrents in preventing the burden of diabetes. [15] This is evidenced by a number of type 2 diabetes patients with several consequences including severe complications, high admission in the hospital, long duration of hospital stay, economic burden, low productivity and health facilities burden.…”
Section: Introductionmentioning
confidence: 99%